Evaporation of a sessile binary droplet on a heated spherical particle - Nguyen, T.; Mitra, S.; Pareek, Vishnu; Joshi, J.; Evans, G. (Elsevier Science Inc., 2018)
© 2018 Elsevier Inc. This study investigated the evaporation behaviour of a binary droplet system (diameter: ~2.6–2.9 mm) comprising water-glycerol mixture (0–35 wt.%) in contact with a spherical particle heated in the range from 323 to 358 K below the saturation temperature of the mixture. Specifically, the effect of liquid composition and particle temperature on both the evaporation rate and temporal variation in droplet temperature were studied. Different approaches to quantify droplet evaporation rate in terms of reduction in volume, equivalent diameter and spherical cap height were analysed. A fairly linear evaporation rate was obtained in all the cases studied. Further, temporal measurements of temperature were obtained at several locations within the droplet under different particle surface temperatures which revealed a short unsteady heating-up period followed by a longer steady state stage. A scaling analysis was performed to predict the unsteady heating time by the thermal diffusion time scale including and excluding the effect of internal convection. Also studied in this work was the variation in surface wettability which was characterised by the wetted area diameter and contact angle. Transient contact angle predicted based on the empirical evaporation model incorporating the Marangoni effect produced good agreement with the experimental data. A linear correlation between the normalised wetted area diameter and the apparent contact angle was obtained. Finally, a brief scaling analysis was presented to quantify various internal motions which showed relative dominance of Marangoni flows in the enhancement of evaporation rate.